2017
DOI: 10.1111/risa.12862
|View full text |Cite
|
Sign up to set email alerts
|

“Birds of a Feather” Fail Together: Exploring the Nature of Dependency in SME Defaults

Abstract: This article studies the effects of incorporating the interdependence among London small business defaults into a risk analysis framework using the data just before the financial crisis. We propose an extension from standard scoring models to take into account the spatial dimensions and the demographic characteristics of small and medium-sized enterprises (SMEs), such as legal form, industry sector, and number of employees. We estimate spatial probit models using different distance matrices based only on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
0
22
0
2
Order By: Relevance
“…Logistic estimations are widely utilized in business‐failure literature (Calabresse et al, 2017). These models are based on variations of the formula below: E Y ) = f ( X ' β ) , where E( Y ) is the expected value of the variable Y , and X false′ β is the linear combination of different explanatory variables X , with unknown β coefficients and f represents the functional form relating both sides of the Equation ().…”
Section: Methodsmentioning
confidence: 99%
“…Logistic estimations are widely utilized in business‐failure literature (Calabresse et al, 2017). These models are based on variations of the formula below: E Y ) = f ( X ' β ) , where E( Y ) is the expected value of the variable Y , and X false′ β is the linear combination of different explanatory variables X , with unknown β coefficients and f represents the functional form relating both sides of the Equation ().…”
Section: Methodsmentioning
confidence: 99%
“…However, both these numbers have been set in a rather arbitrary way, or based upon some empirical but not published procedure [17]. This interdependency has been proven to be a significant factor amongst small and medium-sized enterprises [18]. One of the key challenges in understanding network effects or default propagation in credit scoring concerns the definition of the network itself.…”
Section: Related Workmentioning
confidence: 99%
“…Calabrese, Andreeva, and Ansell () propose a method for detecting the risk of small and medium enterprises’ defaults by considering the enterprises’ location and their demographic characteristics. They found that taking into account this information helped to improve the ability to predict defaults of non‐startups in London.…”
Section: Key Steps and Complexities In Spatial Risk Analysismentioning
confidence: 99%